KONFLIK WADAS DALAM PERSPEKTIF KONFLIK SOSIAL STRUKTURALISME - Ramelan, Michael Sanrio; Suwarno, Panji; Triadi, Irwan; Widodo, Pujo; Sukendro, Achmed (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2024)
This study investigates social conflict in Wadas Village from the perspective of Structuralist social conflict, focusing on interactions between the government and local communities in the context of andesite mining development plans. A qualitative approach with case studies was used to explore the dynamics of this conflict, collecting data from literature studies and involving in-depth interviews with various related parties. Research subjects include the Wadas Village community as a group directly affected and the government as the force that initiates and regulates the development process. This research reveals that these conflicts do not simply stem from individual or local disputes, but more deeply from structural inequalities in access to and control over resources and development decisions. The government, in its role as the highest structure, dominates the development process without adequately considering the interests and aspirations of local communities who are often marginalized. This creates significant tension between the bourgeois class who have greater economic and political access and the proletarian class who rely on local resources for their livelihood. The results of this research highlight the need for structural reforms in development policies that are more inclusive and equitable, as well as increasing community participation in decision making regarding natural resources. The implications of these findings can help in designing policies that are more responsive to local needs, reduce social tensions, and promote economically, socially, and environmentally sustainable development in the region.